Принципы адаптации в защите корпоративных систем - Маслова, Н.А.; Шамаев, В.В. (Штучний інтелект, 2010)
В работе систематизированы основные принципы адаптации, используемые в системах защиты информации, приведена методология построения систем защиты на основе адаптивного подхода, предложена методика оценки эффективности адаптивной системы защиты. Приведены примеры включения интеллектуальных адаптивных систем защиты в корпоративное управление. У роботі систематизовані основні принципи адаптації, які використовуються в системах захисту інформації, наведена методологія побудови систем захисту на основі адаптивного підходу, запропонована методика оцінки ефективності адаптивної системи захисту. Наведені приклади включення інтелектуальних адаптивних систем захисту в корпоративне управління. The basic principles of adaptation, which are used in the security systems of information are systematized, methodology of construction of the security systems on the basis of adaptive approach is described, the method of estimation of efficiency of adaptive security systems is offered in the article. The examples of the intellectual adaptive security systems which are included in a corporate management are described.